Mystical Islam and cosmopolitanism in contemporary German literature : openness to alterity - Twist, Joseph, 1988- (Studies in German literature, linguistics, and culture., 2018)
Highlights the spirituality and cosmopolitanism of four contemporary German Muslim writers, showing that they undermine the ""clash-of-civilizations"" narrative and open up space for new ways of coexisting